Il concetto di diversità nel Dialogo della Terra e della Luna - del Gatto, Antonella (Rivista Internazionale di Studi Leopardiani, 2023)
In the context of a firmly materialistic philosophy and in relation to the eighteenth-century theme of the plurality of worlds, the Dialogo della Terra e della Luna is structurally founded on the recognition of diversity as vital resource. This concept relies on the tendency of matter to aggregation, communication, and thus to the search for the new and the different. The essay aims to show how, even from an intertextual point of view, Leopardi enacts a dialectical confrontation between the principles of uniformity and diversity, which reflects the relation between literature and science and affects the dialogic form of the Operetta.